Increasing the contribution of personal gardening to providing food security - R. F. Gataullin; E. R. Chuvashaeva (Вестник университета)
The article discusses the functional role of personal gardening in ensuring food security in the context of economic sanctions, the historical roots of this institution, and its future. Differences in the interests in gardening among different groups of the population, the formation of production efficiency in various types of farms, and the potential for the development of cooperation, which allows for a more efficient distribution of funds intended to support personal gardening, are analysed. The form of subsistence farming in Russia has changed several times over the last century, especially under the course of collectivisation and during transition to a market economy model. The existing economic distinction between smallholdings in rural areas and collective gardens is now more and more blurred. Compliance with the principle of justice requires appropriate changes in their institutional design. The low production level, the manual labor predominance have been noted that also require changes. The efficiency criterion for personal gardening is cost savings, which differs from the corresponding criterion in the market sector – production profitability. The authors suggest restructuring collective gardens into livable places for our fellow citizens. This requires great deal of work on water supply and sanitation, electricity supply, gas supply, repair and construction of roads, garbage disposal, etc. A successful tool for solving these problems is the experience of the Fund for the Horticultural Associations’ Infrastructure Development in Bashkiria. The creation of service centers for tillage, rental points for small equipment, cooperatives for the sale of surplus products will make it possible to turn orchards into an important source of fruits, vegetables and berries.